Utilization of Internet for Autonomous Learning in Speaking - Witri Handayani (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2015)
Internet use for promoting students’ autonomy in language learning has been a great phenomenon to discuss. Many researches have been conducted about this issue. Now the tendency is pointed out specifically for improving students’ competency in speaking. Speaking is normally learned in the classroom setting in which learners have interlocutor as their speaking partner and under direct supervision from the lecturer. The discussion bellow will concern about some internet links that can be used for speaking study. The learners can study by using these internet links independently and record their own voice and video for their own self- assessment. They choose their own target and links to access and determine their own learning target. In the meantime, they also collect the recording to their teacher for assessment purpose.